A simple infiltrometer automated with a user‐friendly pressure datalogger - Pedro A. M. Leite; Simone Di Prima; Logan M. Schmidt; Bradford P. Wilcox (Vadose Zone Journal)
Abstract We have constructed a new, simplified constant‐head infiltrometer automated with a self‐contained water level datalogger (HOBO U20L‐01) repurposed to measure changes in gas pressure inside an inverted bottle reservoir. Our field tests of six of these infiltrometers confirmed that recorded changes in gas pressure were strongly correlated with changes in water level in the infiltrometer reservoir (R2 = 0.9998). Further, by using the derived experimental calibration function, we were able to obtain accurate near‐steady‐state infiltration rates. This infiltrometer is cheaper and lighter than current commercially available infiltrometers. It can be easily assembled with materials readily available in most hardware stores, and its user‐friendly datalogger does not require any programming knowledge. This infiltrometer is compatible with various ponding infiltration methods, and its generic design allows for modifications with locally available materials to meet diverse research needs.